Dielectrophoresis as a tool for nanoscale DNA manipulation. (15th November 2005) - Tuukkanen, S.; Toppari, J.J.; Hytonen, V.P.; Kuzyk, A.; Kulomaa, M.S.; Torma, P.
The use of the dielectrophoresis as a tool for DNA manipulation is demonstrated experimentally, using both unmodified 48, 500 base pairs long bacteriophage lambda dsDNA (λ-DNA), ∼16 μm in length and 414 base pairs long thiol modified natural dsDNA (avDNA), ∼140 nm in length. We show that both the dsDNA types used, are effectively directed between the planar gold electrodes by the positive dielectrophoresis while applying an AC voltage at frequencies between 500 kHz and 1 MHz. With high concentrations of dsDNA in buffer the attached dsDNA molecules are shown to form bundles or clumps (both λ-DNA and avDNA). Furthermore, we demonstrate the attaching of a single avDNA molecule to an electrode via gold-thiol bonding. Also the clear orientation and straightening along the electric field is seen in this case. In addition, the electrical conductivity of dsDNA is studied by measuring the full I-V characteristics of the samples.